The Effectiveness of Continuous Formative Assessment in Hybrid Learning Models: An Empirical Analysis in Higher Education Institutions - Sri Winarno; Harun Al Azies (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
This study evaluates the effectiveness of Continuous Formative Assessment (CFA) in enhancing student learning outcomes within hybrid learning environments. Data was collected through surveys and tests involving a sample of 120 students. The findings indicate that 85% of students agree or strongly agree that CFA is a beneficial evaluation model for improving learning outcomes. The average score for students' opinions on CFA, based on a 4-point Likert scale, is 3.35 (standard deviation = 0.697), reflecting a positive perception. Additionally, a high average confidence score of 3.78 indicates that students can achieve the necessary learning attainment levels when implementing CFA. The study emphasizes that adopting CFA as a learning evaluation model is beneficial, but it requires lecturers to be dedicated and attentive to its implementation. Lecturers should carefully analyze current educational system policies and their chosen learning strategies. Recommendations for lecturers include integrating CFA with existing educational policies, providing continuous feedback, and adapting teaching methods based on assessment results. This research significantly contributes to the advancement of learning evaluation techniques and highlights CFA's potential impact on hybrid learning models. It underscores the importance of lecturer involvement in effectively implementing CFA and provides insights into students' perceptions and confidence in their learning attainment. The findings suggest that CFA can enhance learning outcomes and student confidence, with implications for future research and practice in educational evaluation and hybrid learning environments.